A wear-resistant geotextile and preparation method thereof
By using the upper and lower protective layers of modified carbon fiber and glass fiber in geotextiles, combined with the modification of iron-boride manganese powder and diamond, the problem of insufficient wear resistance of geotextiles is solved, and its wear resistance and use are significantly improved. life.
Patent Information
- Application Number
- CN202411413557.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing geotextiles have shortcomings in wear resistance, resulting in short service life and inability to meet market demand, reducing their usefulness and usability.
Modified carbon fiber and modified glass fiber are used as the upper and lower protective layers of geotextiles, and modified carbon fibers are modified by grafting PA resins and aminocarbon nanotubes. Diamond and phenolic resins are pretreated by alkali aqueous solution. Modify glass fibers to enhance the wear resistance of geotextiles.
It significantly improves the wear resistance, tear strength and elongation of break of geotextiles, extends the service life and improves the overall performance of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of geotextile preparation, and specifically relates to a wear-resistant geotextile and a preparation method thereof. Background Art
[0002] Geotextile, also known as geotextile, is a permeable geosynthetic material made of synthetic fibers through needle punching or weaving. At present, geotextile is used in the fields of road, railway drainage system, coastal engineering and protective wall. Its application can have the functions of reinforcement, protection, drainage, filtration, isolation and anti-seepage. Isolation effect: Geotextile can isolate building materials with different physical properties, such as soil and sand, soil and concrete, so that these materials will not flow or mix, maintain their respective structures and functions, and thus enhance the bearing capacity of the structure. Filtration (anti-filtration) effect: When water flows from the fine soil layer into the coarse soil layer, geotextile can allow the water to pass smoothly, while effectively intercepting soil particles, fine sand, small stones, etc., to maintain the stability of water and soil engineering. Drainage effect: Geotextile has good water conductivity, can form a drainage channel inside the soil, discharge excess liquid and gas in the soil structure, and help maintain the stability of the soil and the safety of the project. Reinforcement: Geotextiles can enhance the tensile strength and deformation resistance of soil, increase the stability of building structures, improve soil quality, and are suitable for roads, bridges, dams and other projects. Protection: Geotextiles can effectively diffuse, transfer or decompose concentrated stress, prevent soil from being damaged by external forces, and play a role in protecting the soil. In addition, it can also prevent water from scouring the soil.
[0003] Geotextiles are known as the "four major construction" materials together with cement, wood and steel, and can meet the needs of various engineering applications. However, most of the previous geotextiles have poor performance and are easily damaged during use, which reduces the service life of the geotextiles. In addition, many geotextiles have poor wear resistance and cannot meet the needs of today's market, reducing the practicality and usability of geotextiles. Summary of the invention
[0004] The purpose of the present invention is to provide a wear-resistant geotextile and a preparation method thereof in view of the deficiencies of the geotextile in the prior art in terms of wear resistance, etc., wherein modified carbon fiber and modified glass fiber are used as the upper and lower protective layers of the geotextile substrate, respectively, so that the wear resistance and other properties of the geotextile are significantly enhanced.
[0005] A wear-resistant geotextile comprises a wear-resistant layer A, a base body and a wear-resistant layer B from top to bottom; the above layers are fixedly connected; the thickness ratio of the base body, the wear-resistant layer A and the wear-resistant layer B is 1:1.05-1.15:1.1-1.3.
[0006] Furthermore, the wear-resistant layer A is a modified carbon fiber layer; the wear-resistant layer B is a modified glass fiber layer; and the base layer body is a polyester fiber layer.
[0007] The preparation method of the wear-resistant geotextile comprises the following steps:
[0008] S1: preparing a wear-resistant layer A;
[0009] S2: preparing a wear-resistant layer B;
[0010] S3: According to the thickness ratio of 1:1.05-1.15:1.1-1.3, the base body is bonded with the wear-resistant layer A and the wear-resistant layer B respectively, and the wear-resistant geotextile is obtained by heat setting.
[0011] Furthermore, the process of preparing the wear-resistant layer A in step S1 is as follows: by weight, 0.2-0.5 parts of ferric nitrate nonahydrate, 0.3-0.6 parts of manganese nitrate tetrahydrate, 0.1-0.3 parts of sodium borohydride and 0.8-1.4 parts of ammonium carbonate are mixed, microwaved at a power of 800-1200w for 5-10min, crushed and sieved to obtain ferromanganese boride powder; 20-40 parts of carbon fiber, 3-7 parts of ferromanganese boride powder, 4-7 parts of maleic anhydride grafted PA resin and 2-6 parts of amino carbon nanotubes are added to a twin-screw extruder, mixed at a temperature of 220-240°C for 1-3h and then extruded; spinning at a temperature of 240-260°C, with a needle punching density of 35-45 needles / cm 2 The wear-resistant layer A is obtained by needling with a depth of 5-9 mm.
[0012] Furthermore, the preparation of the wear-resistant layer A in step S1 is further optimized as follows: by weight, 0.4 parts of ferric nitrate nine hydrate, 0.5 parts of manganese nitrate tetrahydrate, 0.2 parts of sodium borohydride and 1.2 parts of ammonium carbonate are mixed, microwaved at a power of 1000w for 7min, crushed and sieved to obtain ferromanganese boride powder; 35 parts of carbon fiber, 6 parts of ferromanganese boride powder, 5 parts of maleic anhydride grafted PA resin and 4 parts of amino carbon nanotubes are added to a twin-screw extruder, mixed at a temperature of 235°C for 2.5h and then extruded; spinning at a temperature of 250°C, with a needle density of 40 needles / cm 2 The wear-resistant layer A was obtained by needling with a depth of 8 mm.
[0013] Furthermore, the process of preparing the wear-resistant layer B in step S2 is: adding nanodiamonds to a sodium hydroxide aqueous solution with a mass fraction of 15-25% according to a solid-liquid ratio of 1g:3-6ml, and ultrasonically treating at a power of 300-500W for 5-8min; stirring at a temperature of 80-110°C for 40-60min; obtaining pretreated diamonds after washing and drying; taking 25-45 parts of glass fiber, 4-7 parts of pretreated diamonds, 3-7 parts of phenolic resin and 1-3 parts of polyetheretherketone, mixing at a temperature of 190-210°C for 2-4h and then extruding; spinning at a temperature of 220-240°C, and obtaining a wear-resistant layer A with a needle density of 40-50 needles / cm2 and a needle depth of 10-13mm.
[0014] Furthermore, the preparation of the wear-resistant layer B in step S2 is further optimized as follows: adding nanodiamond to a sodium hydroxide aqueous solution with a mass fraction of 22% according to a solid-liquid ratio of 1g:4.5ml, and ultrasonically treating at a power of 450W for 7min; stirring at a temperature of 105°C at a rate of 600r / min for 55min; obtaining pretreated diamond after washing and drying; taking 40 parts of glass fiber, 6 parts of pretreated diamond, 5 parts of phenolic resin and 2 parts of polyetheretherketone, mixing at a temperature of 205°C for 3.5h and then extruding; spinning at a temperature of 235°C, with a needle density of 45 needles / cm 2 The wear-resistant layer B was obtained by needling at a depth of 12 mm.
[0015] Furthermore, in step S3, the base body and the wear-resistant layer A and the wear-resistant layer B are needle-punched respectively at a thickness ratio of 1:1.1:1.2, and heat-set at a temperature of 100-120° C. for 45-75 minutes to obtain the wear-resistant geotextile.
[0016] Furthermore, the wear-resistant geotextile is obtained by heat setting at a temperature of 110° C. for 60 minutes.
[0017] Furthermore, the acupuncture density during the acupuncture process is 85 needles / cm 2 , the acupuncture depth is 14mm.
[0018] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0019] The present invention adopts ferromanganese boride powder, maleic anhydride grafted PA resin and amino carbon nanotubes to modify carbon fibers, and the wear resistance is improved by cross-linking the maleic anhydride grafted PA resin and the amino carbon nanotubes. At the same time, under the synergistic effect of ferromanganese boride powder, the wear resistance is further improved; diamond is pretreated with an alkaline aqueous solution, and the glass fiber is modified together with phenolic resin, polyetheretherketone, etc. to improve the wear resistance of the glass fiber; and the wear-resistant layer B and the wear-resistant layer A are respectively arranged on the upper and lower sides of the base body, so that the wear resistance of the overall geotextile material is significantly enhanced. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The sources of raw materials used in the present invention are as follows:
[0022] Carbon fiber comes from Wuhan Jiyesheng Chemical Co., Ltd. with item number A01108; maleic anhydride grafted PA resin comes from Dongguan Shenghao Plastic Raw Materials Co., Ltd. with item number 5541254; amino carbon nanotubes come from Hubei Chengfeng Chemical Co., Ltd. with item number CF2023229; glass fiber comes from Shanghai Yuanye Biotechnology Co., Ltd. with item number S30527; phenolic resin comes from Shandong Suihua Biotechnology Co., Ltd. with item number 1996; polyetheretherketone comes from Wuhan Haishan Technology Co., Ltd. with item number 1638.
[0023] Example 1
[0024] The present invention provides a method for preparing a wear-resistant geotextile, comprising the following steps:
[0025] S1: 0.2g of ferric nitrate nonahydrate, 0.3g of manganese nitrate tetrahydrate, 0.1g of sodium borohydride and 0.8g of ammonium carbonate were mixed, microwaved at a power of 800w for 5min, crushed and sieved to obtain ferromanganese boride powder; 20g of carbon fiber, 3g of ferromanganese boride powder, 4g of maleic anhydride grafted PA resin and 2g of amino carbon nanotubes were added to a twin-screw extruder, mixed at a temperature of 220℃ for 1h and then extruded; spinning was carried out at a temperature of 240℃, with a needle punching density of 35 needles / cm 2 , the needle-punching depth is 5 mm to obtain the wear-resistant layer A;
[0026] S2: Add nanodiamond to a 15% sodium hydroxide aqueous solution at a solid-liquid ratio of 1g:3ml, and ultrasonically treat for 5min at a power of 300W; stir at a temperature of 80℃ and a speed of 500r / min for 40min; wash and dry at 80℃ to obtain pretreated diamond; take 25g glass fiber, 4g pretreated diamond, 3g phenolic resin and 1g polyetheretherketone, mix at a temperature of 190℃ for 2h and then extrude; spin at a temperature of 220℃ and punch at a density of 40 needles / cm 2 , the needle-punching depth is 10 mm to obtain the wear-resistant layer B;
[0027] S3: The base body and the wear-resistant layer A and the wear-resistant layer B were needle-punched at a thickness ratio of 1:1.1:1.2, and heat-set at 100°C for 45 minutes. The needle-punching density was 85 needles / cm 2, the needle punching depth is 14 mm, and the wear-resistant geotextile is obtained.
[0028] Example 2
[0029] The present invention provides a method for preparing a wear-resistant geotextile, comprising the following steps:
[0030] S1: 0.5g of ferric nitrate nonahydrate, 0.6g of manganese nitrate tetrahydrate, 0.3g of sodium borohydride and 1.4g of ammonium carbonate were mixed, microwaved at a power of 1200w for 10min, crushed and sieved to obtain ferromanganese boride powder; 40g of carbon fiber, 7g of ferromanganese boride powder, 7g of maleic anhydride grafted PA resin and 6g of amino carbon nanotubes were added to a twin-screw extruder, mixed at a temperature of 240℃ for 3h and then extruded; spinning was carried out at a temperature of 260℃, and the needle punching density was 45 needles / cm 2 , the needle-punching depth is 9 mm to obtain the wear-resistant layer A;
[0031] S2: Add nanodiamond to 25% sodium hydroxide aqueous solution at a solid-liquid ratio of 1g:6ml, and ultrasonically treat for 8min at a power of 500W; stir at a temperature of 110℃ and a speed of 800r / min for 60min; obtain pretreated diamond after washing and drying; take 45g glass fiber, 7g pretreated diamond, 7g phenolic resin and 3g polyetheretherketone, mix at a temperature of 210℃ for 4h and then extrude; spin at a temperature of 240℃ and punch at a density of 50 needles / cm 2 , the needle-punching depth is 13 mm to obtain the wear-resistant layer B;
[0032] S3: The base body and the wear-resistant layer A and the wear-resistant layer B were needle-punched at a thickness ratio of 1:1.1:1.2, and heat-set at 120°C for 75 minutes. The needle-punching density was 85 needles / cm 2 , the needle punching depth is 14 mm, and the wear-resistant geotextile is obtained.
[0033] Example 3
[0034] The present invention provides a method for preparing a wear-resistant geotextile, comprising the following steps:
[0035] S1: 0.4g of ferric nitrate nonahydrate, 0.5g of manganese nitrate tetrahydrate, 0.2g of sodium borohydride and 1.2g of ammonium carbonate were mixed, microwaved at a power of 1000w for 7min, crushed and sieved to obtain ferromanganese boride powder; 35g of carbon fiber, 6g of ferromanganese boride powder, 5g of maleic anhydride grafted PA resin and 4g of amino carbon nanotubes were added to a twin-screw extruder, mixed at a temperature of 235℃ for 2.5h and then extruded; spinning was carried out at a temperature of 250℃, with a needle punching density of 40 needles / cm 2 , the needle-punching depth is 8 mm to obtain the wear-resistant layer A;
[0036] S2: Add nanodiamond to a 22% sodium hydroxide aqueous solution at a solid-liquid ratio of 1g:4.5ml, and ultrasonically treat for 7min at a power of 450W; stir at a temperature of 105℃ and a speed of 600r / min for 55min; wash and dry at 85℃ to obtain pretreated diamond; take 40g glass fiber, 6g pretreated diamond, 5 phenolic resin and 2g polyetheretherketone, mix at a temperature of 205℃ for 3.5h and then extrude; spin at a temperature of 235℃ and punch at a density of 45 needles / cm 2 , the needle-punching depth is 12 mm to obtain the wear-resistant layer B;
[0037] S3: The base body and the wear-resistant layer A and the wear-resistant layer B were needle-punched at a thickness ratio of 1:1.1:1.2, and heat-set at 110°C for 60 minutes. The needle-punching density was 85 needles / cm 2 , the needle punching depth is 14 mm, and the wear-resistant geotextile is obtained.
[0038] Comparative Example 1
[0039] The difference between this comparative example and Example 1 is that no ferromanganese boride powder is added in step S1, and the other steps are the same.
[0040] Comparative Example 2
[0041] The difference between this comparative example and Example 1 is that no maleic anhydride grafted PA resin is added in step S1, and the other steps are the same.
[0042] Comparative Example 3
[0043] The difference between this comparative example and Example 1 is that no amino-treated carbon nanotubes are added in step S1, and the other steps are the same.
[0044] Comparative Example 4
[0045] The difference between this comparative example and Example 1 is that in step S2, sodium hydroxide aqueous solution is not used to pretreat diamond, and the other steps are the same.
[0046] Comparative Example 5
[0047] The difference between this comparative example and Example 1 is that no phenolic resin is added in step S2, and the other steps are the same.
[0048] Comparative Example 6
[0049] The difference between this comparative example and Example 1 is that polyetheretherketone is not added in step S2, and the other steps are the same.
[0050] Performance Test:
[0051] The wear rate was tested according to GB / T3960-2016; the tear strength / KN was measured according to GB / T 13763-1992; and the elongation at break was tested according to ISO 527-2-2012. The test results are shown in Table 1 below.
[0052] Table 1 Performance test results
[0053]
[0054] It can be seen from the above performance test results that the wear resistance, tear strength and elongation at break of Examples 1-3 are relatively good. In particular, the comprehensive performance of Example 3 is the most outstanding. Compared with the Examples, the Comparative Examples are significantly worse than the Examples in the corresponding performance tests due to the differences in the composition of each component and the preparation process. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0055] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A wear-resistant geotextile, characterized in that: It includes wear-resistant layer A, base body and wear-resistant layer B from top to bottom; the above layers are fixedly connected; the thickness ratio of base body, wear-resistant layer A and wear-resistant layer B is 1:1.05-1.15:1.1-1.3; The wear-resistant layer A is a modified carbon fiber layer; the wear-resistant layer B is a modified glass fiber layer; the base layer body is a polyester fiber layer; The process of preparing the wear-resistant layer A is as follows: 0.2-0.5 parts of ferric nitrate nine hydrate, 0.3-0.6 parts of manganese nitrate tetrahydrate, 0.1-0.3 parts of sodium borohydride and 0.8-1.4 parts of ammonium carbonate are mixed by weight, and microwaved at a power of 800-1200w for 5-10min, and then crushed and sieved to obtain ferromanganese boride powder; 20-40 parts of carbon fiber, 3-7 parts of ferromanganese boride powder, 4-7 parts of maleic anhydride grafted PA resin and 2-6 parts of amino carbon nanotubes are added to a twin-screw extruder, mixed at a temperature of 220-240°C for 1-3h and then extruded; spinning at a temperature of 240-260°C, and needle punching density of 35-45 needles / cm 2 , the needle-punching depth is 5-9 mm to obtain the wear-resistant layer A; The process of preparing the wear-resistant layer B is as follows: adding nano-diamond to a sodium hydroxide aqueous solution with a mass fraction of 15-25% according to a solid-liquid ratio of 1g:3-6ml, ultrasonically treating at a power of 300-500W for 5-8min; stirring at a temperature of 80-110°C for 40-60min; washing and drying to obtain pre-treated diamond; taking 25-45 parts of glass fiber, 4-7 parts of pre-treated diamond, 3-7 parts of phenolic resin and 1-3 parts of polyetheretherketone, mixing at a temperature of 190-210°C for 2-4h and then extruding; spinning at a temperature of 220-240°C, and punching at a density of 40-50 needles / cm 2 The wear-resistant layer B is obtained by needling at a depth of 10-13 mm.
2. A method for preparing a wear-resistant geotextile, characterized in that: The steps include: S1: preparing a wear-resistant layer A; S2: preparing a wear-resistant layer B; S3: bonding the base body to the wear-resistant layer A and the wear-resistant layer B respectively according to a thickness ratio of 1:1.05-1.15:1.1-1.3, and obtaining the wear-resistant geotextile by heat setting; The wear-resistant layer A is a modified carbon fiber layer; the wear-resistant layer B is a modified glass fiber layer; the base layer body is a polyester fiber layer; The process of preparing the wear-resistant layer A in step S1 is as follows: 0.2-0.5 parts of ferric nitrate nine hydrate, 0.3-0.6 parts of manganese nitrate tetrahydrate, 0.1-0.3 parts of sodium borohydride and 0.8-1.4 parts of ammonium carbonate are mixed by weight, and microwaved at a power of 800-1200w for 5-10min, and then crushed and sieved to obtain ferromanganese boride powder; 20-40 parts of carbon fiber, 3-7 parts of ferromanganese boride powder, 4-7 parts of maleic anhydride grafted PA resin and 2-6 parts of amino carbon nanotubes are added to a twin-screw extruder, mixed at a temperature of 220-240°C for 1-3h and then extruded; spinning at a temperature of 240-260°C, and needle punching density of 35-45 needles / cm 2 , the needle-punching depth is 5-9 mm to obtain the wear-resistant layer A; The process of preparing the wear-resistant layer B in step S2 is as follows: adding nanodiamond to a sodium hydroxide aqueous solution with a mass fraction of 15-25% according to a solid-liquid ratio of 1g:3-6ml, and ultrasonically treating at a power of 300-500W for 5-8min; stirring at a temperature of 80-110°C for 40-60min; washing and drying to obtain pretreated diamond; taking 25-45 parts of glass fiber, 4-7 parts of pretreated diamond, 3-7 parts of phenolic resin and 1-3 parts of polyetheretherketone, mixing at a temperature of 190-210°C for 2-4h and then extruding; spinning at a temperature of 220-240°C, and punching at a density of 40-50 needles / cm 2 The wear-resistant layer B is obtained by needling at a depth of 10-13 mm.
3. The method for preparing a wear-resistant geotextile according to claim 2, characterized in that: Preparation of the wear-resistant layer A in step S1 is further optimized as follows: by weight, 0.4 parts of ferric nitrate nine hydrate, 0.5 parts of manganese nitrate tetrahydrate, 0.2 parts of sodium borohydride and 1.2 parts of ammonium carbonate are mixed, microwaved at a power of 1000w for 7min, crushed and sieved to obtain ferromanganese boride powder; 35 parts of carbon fiber, 6 parts of ferromanganese boride powder, 5 parts of maleic anhydride grafted PA resin and 4 parts of amino carbon nanotubes are added to a twin-screw extruder, mixed at a temperature of 235°C for 2.5h and then extruded; spinning at a temperature of 250°C, with a needle density of 40 needles / cm 2 The wear-resistant layer A was obtained by needling with a depth of 8 mm.
4. The method for preparing a wear-resistant geotextile according to claim 2, characterized in that: The preparation of the wear-resistant layer B in step S2 is further optimized as follows: adding nanodiamond to a sodium hydroxide aqueous solution with a mass fraction of 22% according to a solid-liquid ratio of 1g:4.5ml, and ultrasonically treating at a power of 450W for 7min; stirring at a temperature of 105°C and a speed of 600r / min for 55min; washing and drying to obtain pretreated diamond; taking 40 parts of glass fiber, 6 parts of pretreated diamond, 5 parts of phenolic resin and 2 parts of polyetheretherketone, mixing at a temperature of 205°C for 3.5h and then extruding; spinning at a temperature of 235°C, with a needle density of 45 needles / cm 2 The wear-resistant layer B was obtained by needling at a depth of 12 mm.
5. The method for preparing a wear-resistant geotextile according to claim 2, characterized in that: In step S3, the base body and the wear-resistant layer A and the wear-resistant layer B are needle-punched respectively according to a thickness ratio of 1:1.1:1.2, and heat-set at a temperature of 100-120° C. for 45-75 minutes to obtain the wear-resistant geotextile.
6. The method for preparing a wear-resistant geotextile according to claim 5, characterized in that: The wear-resistant geotextile is obtained by heat setting at a temperature of 110° C. for 60 minutes.
7. The method for preparing a wear-resistant geotextile according to claim 5 or 6, characterized in that: The acupuncture density during the acupuncture process is 85 needles / cm 2 , the acupuncture depth is 14mm.
Citation Information
Patent Citations
Preparation method of high-strength weather-proof type geotextile
CN106381610A
Wearing-resistant geotechnical cloth and preparation method thereof
CN107936339A
